The German–Austrian S3 Guideline “Cardiogenic Shock Due to Myocardial Infarction: Diagnosis, Monitoring, and Treatment” - Pilarczyk, Kevin; Werdan, Karl; Russ, Martin; Thiele, Holger; Michels, Guido; Boeken, Udo; Thielmann, Matthias (The Thoracic and Cardiovascular Surgeon, 2020)
Despite advances in the treatment of acute myocardial infarction with subsequent mortality reduction, which are mainly caused by the early timing of revascularization, cardiogenic shock still remains the leading cause of death with mortality rates still approaching 40 to 50%. Cardiogenic shock is characterized by a multiorgan dysfunction syndrome, often complicated by a systemic inflammatory response syndrome that affects the outcome more than the reduction of the cardiac contractile function. However, both European and American guidelines on myocardial infarction focus on interventional or surgical aspects only. Therefore, experts from eight German and Austrian specialty societies including the German Society for Thoracic and Cardiovascular Surgery published the German–Austrian S3 guideline “cardiogenic shock due to myocardial infarction: diagnosis, monitoring, and treatment” to provide evidence-based recommendations for the diagnosis and treatment of infarction-related cardiogenic shock in 2010 covering the topics of early revascularization, revascularization techniques, intensive care unit treatment including ventilation, transfusion regimens, adjunctive medical therapy, and mechanical support devices. Within the last 3 years, this guideline was updated as some major recommendations were outdated, or new evidence had been found. This review will therefore outline the management of patients with cardiogenic shock complicating acute myocardial infarction according to the updated guideline with a major focus on evidence-based recommendations which have been found relevant for cardiac surgery.
Keywords: cardiogenic shock; myocardial infarction; guideline; percutaneous coronary intervention; coronary artery bypass graft; extracorporeal; multiorgan dysfunction syndrome; extracorporeal membrane oxygenation; intra-aortic balloon counterpulsation; ventricular assist device